Seneca's De Ira: a study - Smith, A (2015)
This thesis offers new philosophical and literary interpretations of Seneca's De ira. It takes as its starting-point the observation that both the philosophical position on which the text relies and the way in which it is organised appear to be chaotic, and it investigates how far and why this is the case. It shows that a coherent philosophical position underlies the text but that the text presents it as incoherent, and that it does this for therapeutic purposes. Similarly, it shows that the text is organised in a far more orderly way than has been previously appreciated, and it explains how the (apparent) disruption of that organisational system serves the text's therapeutic function. In making these arguments, it presents new readings of the De ira that reveal the text's philosophical and literary qualities, arguing that it constitutes a more sophisticated response to Seneca’s philosophical predecessors than previous accounts have claimed, and that the text, as it progresses, introduces new therapeutic strategies that provide 'safety nets' should its earlier principal strategies have failed. The thesis aims to be methodologically innovative in using Seneca’s descriptions of emotional responses as well as more explicit theorising to reconstruct his philosophical position and in suggesting a new approach to interpreting the role of interlocutors and addressees in didactic and dialogic texts.